Maturity analysis in project management in Colombian universities (2018)
Project management has become a worldwide trend within organizations seeking continuous improvement of their processes, where maturity models for project management play an important role. The general objective of the research is to evaluate the degree of maturity in project management in order to propose strategies to improve the organizational culture in project management. The selection of the maturity model that fits the organizational context is carried out, then an analysis is made of the management of those involved and the management of communication in project matters, the degree of maturity is measured, and then strategies for improvement are selected. As a result of the research it was obtained that reaching a level of maturity implies obtaining results from a measurement and comparing them with a previously established standard, in order to implement best practices, reach a higher level of scale or continuously improve their processes. However, it should be borne in mind that reaching maturity involves a gradual process, senior management support, time and a highly trained team.